2017
DOI: 10.1007/s10529-017-2402-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and genetically engineered oils as replacements for fish oil in aquaculture feeds

Abstract: As the global population grows more of our fish and seafood are being farmed. Fish are the main dietary source of the omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFA), eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids, but these cannot be produced in sufficient quantities as are now required for human health. Farmed fish have traditionally been fed a diet consisting of fishmeal and fish oil, rich in n-3 LC-PUFA. However, the increase in global aquaculture production has resulted in these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 67 publications
(95 reference statements)
1
86
1
2
Order By: Relevance
“…As such, they are now cultivated heterotrophically in the absence of light in large-scale fermentation systems using organic carbon sources for industrial production of food-grade DHA and are available commercially in various processed forms (e.g., whole-cell lipid-rich powders, extracted oil emulsions, etc.). The aquaculture feed market is in desperate need of these DHA-rich oils as the Global Salmon Initiative (GSI) has indicated that its members could immediately take up 200,000 t annually of this novel alternative lipid source if it were available [6].…”
Section: Arthrospira Chlorella Entomoneis Haematococcus Isochrysis Namentioning
confidence: 99%
“…As such, they are now cultivated heterotrophically in the absence of light in large-scale fermentation systems using organic carbon sources for industrial production of food-grade DHA and are available commercially in various processed forms (e.g., whole-cell lipid-rich powders, extracted oil emulsions, etc.). The aquaculture feed market is in desperate need of these DHA-rich oils as the Global Salmon Initiative (GSI) has indicated that its members could immediately take up 200,000 t annually of this novel alternative lipid source if it were available [6].…”
Section: Arthrospira Chlorella Entomoneis Haematococcus Isochrysis Namentioning
confidence: 99%
“…The European Food Safety Agency have approved health claims in relation to foods naturally rich or fortified with EPA and DHA. Microalgal oils have recently emerged to offer a sustainable alternative source of EPA and DHA that is also suitable for vegetarians and vegans …”
Section: Introductionmentioning
confidence: 99%
“…Microalgal oils have recently emerged to offer a sustainable alternative source of EPA and DHA that is also suitable for vegetarians and vegans. [9][10][11] Nanoemulsions, similar to conventional oil-in-water emulsion systems but with considerably smaller droplet sizes, can be used to incorporate lipid-based components into aqueous foods. 12 The use of nanoemulsions offers potential benefits, including increases in water dispersibility of oils, good physical and chemical stability, and improved bioavailability of various hydrophobic lipid components.…”
Section: Introductionmentioning
confidence: 99%
“…Most of marine fish have to ingest LC‐PUFA from their diets since their fatty acid desaturases and/or ELOVL5 are not efficient enough to produce LC‐PUFA from the SC‐PUFA, which are different from freshwater fish . Fish oil is rich in LC‐PUFA and the main source of LC‐PUFA of humans and other animals . However, the source of fish oil is limited with the rapid development of marine aquaculture .…”
Section: Introductionmentioning
confidence: 99%
“…Fish oil is rich in LC‐PUFA and the main source of LC‐PUFA of humans and other animals . However, the source of fish oil is limited with the rapid development of marine aquaculture . Fish oil has to be substituted for aquaculture and plant oil is a good substitute of fish oil .…”
Section: Introductionmentioning
confidence: 99%